Standards for thyroid laboratory testing, and cognitive functions after menopause - Bojar, Iwona; Bejga, Przemysław; Witczak, Mariusz; Łyszcz, Robert; Makara-Studzinska, Marta (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction : The aim of the study is to analyze the relationship between normative and non-normative thyroid tests (TSH, TT4, TT3, FT3, FT4, anti-TPO, anti-Tg, AB-TSHR) and the level of cognitive functions in postmenopausal women. Material and methods: The study group consisted of 383 women from south-eastern Poland, aged 50-65 years. The cognitive functions were evaluated using a diagnostic instrument – Central Nervous System – Vital Signs (CNS-VS). Blood was collected for determination of the following parameters: TSH, TT4, TT3, FT3, FT4, anti-TPO, anti-Tg, AB-TSHR. Results: There were significant differences in NCI, executive functions, psychomotor speed, reaction time, complex attention and cognitive flexibility, depending on the normative and non-normative level of TSH. Women whose level of FT3 was at the lower limit of the normal range obtained poorer results in psychomotor speed, while subjects with levels of FT4 below the standard achieved significantly lower scores for this function. The relationship between NCI and cognitive functions, and the normative and non-normative anti-TPO results, showed significant differences in verbal memory, visual memory, processing speed and reaction time. The level of AB-TSHR reported as normal or above the norm significantly differentiated from the results of NCI, processing speed, executive functions, psychomotor speed, complex attention and cognitive flexibility. Conclusions : Concentrations of laboratory parameters assessing the thyroid function located within the upper limits of the normal range showed a different relationship with the cognitive performance than concentrations located within the lower limits of the standard.